1999
DOI: 10.1039/a906687j
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanisms of the reverse Boudouard reaction over metal carbonates in connection with the reactions of solid carbon with the metal carbonates

Abstract: The decomposition processes of alkali or alkaline earth carbonates with a large excess of carbon, and the reverse Boudouard reaction given by over metal carbonates, were compared. The carbonates of CO 2 /C ] 2CO Li`, Na`, K`, Cs`, Sr2`and Ba2`generated CO exclusively by an intermolecular redox reaction given byThe reverse Boudouard reaction over these metal carbonates at 700 ¡C proceeded CO 3 2~] C ] 2CO ] O2~. at a steady rate until just before the carbon was completely consumed, and in the cases of Li`, Sr2`… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 23 publications
3
55
0
Order By: Relevance
“…Nagase et al, [26] postulated a cyclic catalytic scheme for the CO 2 reforming of carbon. In this scheme, the reaction of carbon with Na 2 CO 3 results in the formation of oxides of sodium [Eqs.…”
Section: Influence Of Na 2 Co 3 On Gasificationmentioning
confidence: 99%
“…Nagase et al, [26] postulated a cyclic catalytic scheme for the CO 2 reforming of carbon. In this scheme, the reaction of carbon with Na 2 CO 3 results in the formation of oxides of sodium [Eqs.…”
Section: Influence Of Na 2 Co 3 On Gasificationmentioning
confidence: 99%
“…The other case is characterized by the generation of CO through an intra-molecular redox process, as has been shown in the case of alkali or alkaline earth carbonates in the literature [20]. The carbonate decomposition which leads to the CO formation given by (6) is initiated by intermolecular electron transfer from a reducing agent to CO 3 2-.…”
Section: Fuel Gasificationmentioning
confidence: 99%
“…Nagase et al [6] reported that different oxidation mechanisms act in the combination of carbon with Li 2 CO 3 and Na 2 CO 3 . Carbon with Li 2 CO 3 is oxidized by the following intermolecular redox reaction:…”
Section: Introductionmentioning
confidence: 99%